High-throughput functional assay in cystic fibrosis patient-derived organoids allows drug repurposing. Issue 1 (30th January 2023) - Spelier, Sacha; de Poel, Eyleen; Ithakisiou, Georgia N.; Suen, Sylvia W.F.; Hagemeijer, Marne C.; Muilwijk, Danya; Vonk, Annelotte M.; Brunsveld, Jesse E.; Kruisselbrink, Evelien; van der Ent, Cornelis K.; Beekman, Jeffrey M.
Background: Cystic fibrosis (CF) is a rare hereditary disease caused by mutations in the cystic fibrosis transmembrane conductance regulator ( CFTR ) gene. Recent therapies enable effective restoration of CFTR function of the most common F508del CFTR mutation. This shifts the unmet clinical need towards people with rare CFTR mutations such as nonsense mutations, of which G542X and W1282X are most prevalent. CFTR function measurements in patient-derived cell-based assays played a critical role in preclinical drug development for CF and may play an important role to identify new drugs for people with rare CFTR mutations. Methods: Here, we miniaturised the previously described forskolin-induced swelling (FIS) assay in intestinal organoids from a 96-well to a 384-well plate screening format. Using this novel assay, we tested CFTR increasing potential of a 1400-compound Food and Drug Administration (FDA)-approved drug library in organoids from donors with W1282X/W1282X CFTR nonsense mutations. Results: The 384-well FIS assay demonstrated uniformity and robustness based on coefficient of variation and Z'-factor calculations. In the primary screen, CFTR induction was limited overall, yet interestingly, the top five compound combinations that increased CFTR function all contained at least one statin. In the secondary screen, we indeed verified that four out of the five statins (mevastatin, lovastatin, simvastatin and fluvastatin) increased CFTR function when combined with CFTR modulators. Statin-induced CFTR rescue was concentration-dependent and W1282X-specific. Conclusions: Future studies should focus on elucidating genotype specificity and mode-of-action of statins in more detail. This study exemplifies proof of principle of large-scale compound screening in a functional assay using patient-derived organoids. This study established a high-throughput functional assay using CF patient-derived intestinal organoids. 1400 FDA-approved compounds were screened, and it was found that statins increased function of W1282X/W1282X CFTR when combined with CFTR modulators. https://bit.ly/3NPXvhf